The Impact of Profit Shifting on Economic Activity and Tax Competition - Klemm, Alexander (IMF Working Papers; Working Paper ;, 2019)
A growing empirical literature has documented significant profit shifting activities by multinationals. This paper looks at the impact of such profit shifting on real activity and tax competition. Real activity can be affected as profit shifting changes-and theoretically most likely reduces-the cost of capital. Tax competition, even over real capital, is affected, because a permissive attitude toward profit shifting can be seen as a selective tax reduction for multinationals. Tightening profit shifting rules in turn can affect tax competition through the main rate. This paper discusses these issues theoretically and with the help of a simulation to assess the impact of profit-shifting on investment, revenues, and government behavior. Using the theoretical framework, it also provides a brief overview of the related empirical literature.